A comprehensive analysis of aerodynamic flow around H-Darrieus rotor with camber-bladed profile. Issue 5 (October 2019) - Souaissa, Khaled; Ghiss, Moncef; Chrigui, Mouldi; Bentaher, Hatem; Maalej, Aref
Improving the H-Darrieus rotor is often followed by the investigation of the influence of the turbine's parameter design, notably, the aspect ratio, the solidity ( σ ), the tip speed ratio, and the airfoil profile shape. In this work, we are interested in both the aerodynamic flows around a straight cambered blade profile and the rotor turbine wake separation of a Darrieus vertical axis wind turbine. The aim of this study is to better understand the evolution of the instantaneous torque and the generated-separated blade vortex during full rotation. Indeed, a three-dimensional computational fluid dynamics model of a vertical axis wind turbine with a straight cambered blade profile NACA4312 operating over a large range of tip speed ratio is considered. The flows are governed by Reynolds-averaged Navier–Stokes equations and the turbulence is modeled with shear stress transport formulations k - ω . This research revealed a high correlation between the evolution of the torque coefficient and the generated-separated blades vortex. In particular, a good correlation between the maximum tip vortices size and the torque coefficient peak is demonstrated.